Impact of a mid‐urethral synthetic mesh sling on long‐term risk of systemic conditions in women with stress urinary incontinence: a national cohort study. (5th October 2021) - Muller, P; Gurol‐Urganci, I; Thakar, R; Ehrenstein, MR; Van Der Meulen, J; Jha, S
Abstract : Objective: To compare the incidence of systemic conditions between women who had surgical treatment for stress incontinence with mesh and without mesh. Design: National cohort study. Setting: English National Health Service. Population: Women with no previous record of systemic disease who had first‐time urinary incontinence surgery between 1 January 2006 and 31 December 2013, followed up to the earliest of 10 years or 31 March 2019. Methods: Competing‐risks regression was used to estimate hazard ratios (HR), adjusted for patient characteristics, with HR > 1 indicating increased incidence following mesh surgery. Main outcome measures: First postoperative admission with a record of autoimmune disease, fibromyalgia or myalgic encephalomyelitis up to 10 years following the first incontinence procedure. Results: The cohort included 88 947 women who had mesh surgery and 3389 women who had non‐mesh surgery. Both treatment groups were similar with respect to age, socio‐economic deprivation, comorbidity and ethnicity. The 10‐year cumulative incidence of autoimmune disease, fibromyalgia or myalgic encephalomyelitis was 8.1% (95% CI 7.9–8.3%) in the mesh group and 9.0% (95% CI 8.0–10.1%) in the non‐mesh group (adjusted HR 0.89, 95% CI 0.79–1.01; P  = 0.07). A sensitivity analysis including only autoimmune diseases as an outcome returned a similar result. Conclusions: These findings do not support claims that synthetic mesh slings cause systemic disease. Tweetable abstract: No evidence of increased risk of systemic conditions after stress incontinence treatment with a mesh sling. Tweetable abstract: No evidence of increased risk of systemic conditions after stress incontinence treatment with a mesh sling.